ASEAN-China Free Trade Agreement (ACFTA) dan Penyelundupan Tekstil Asal Tiongkok di Indonesia - Agustina, Dyah Ayu; Windiani, Reni (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
This thesis aims is to analyze the effect of trade agreement between Indonesia and China in ASEAN-China Free Trade Agreement (ACFTA) for smuggling of Chinese textile in Indonesia on 2015-2017. This thesis begins with the descriptions of textile trading’s conditions respectively in Indonesia and China, textile trading between the two countries, textile trading between China and ASEAN, and an explanation of information on Chinese textile smuggling that occurred in the port of Batam. This research’s methode uses qualitative method with explanative type of research and analyzed by collecting data obtained from interviews, books, journals, reports of previous researchers and mass media. The range of research on this screening is from 2015 to 2017. The explanation of the effect of ACFTA on Chinese textile smuggling in Indonesia uses neoliberalism theory and the concept of free trade and deregulation. The results of this study indicate that the concept of deregulation in ACFTA is realized by the decrease of Chinese textile import duty to 0% makes Chinese textile imports in Indonesia cheaper than the domestic. This has resulted in losses for textile businessmen and guiding them to find ways to avoid losses by smuggling Chinese textiles through the port of Batam.